2015
DOI: 10.18632/oncotarget.5845
|View full text |Cite
|
Sign up to set email alerts
|

Whole-exome sequencing and genome-wide methylation analyses identify novel disease associated mutations and methylation patterns in idiopathic hypereosinophilic syndrome

Abstract: A thorough understanding of the idiopathic hypereosinophilic syndrome (IHES) and further optimization of diagnostic work-up procedures are warranted. We analyzed purified eosinophils from patients with IHES by next-generation whole-exome sequencing and compared DNA methylation profiles from reactive eosinophilic conditions to known clonal and suspected clonal eosinophilia. Somatic missense mutations in cancer-related genes were detected in three IHES patients. These included the spliceosome gene PUF60 and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
(41 reference statements)
0
13
0
Order By: Relevance
“…Recently, Anderson and colleagues 26 isolated eosinophils and performed whole genome sequencing in five patients with idiopathic hypereosinophilic syndrome. Somatic missense mutations were found in three patients, Figure 2 Patients with chronic eosinophilic leukemia, not otherwise specified showed a median disease-specific survival of 14.4 months (1.0-120.1 months), significantly inferior to patients with idiopathic hypereosinophilic syndrome with no identifiable mutations (median disease-specific survival: not reached, 0.6-405.3 months, P o0.001), but not statistically different from idiopathic hypereosinophilic syndrome patients with mutations (not reached, 1.0-223.9 months, P = 0.117).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Anderson and colleagues 26 isolated eosinophils and performed whole genome sequencing in five patients with idiopathic hypereosinophilic syndrome. Somatic missense mutations were found in three patients, Figure 2 Patients with chronic eosinophilic leukemia, not otherwise specified showed a median disease-specific survival of 14.4 months (1.0-120.1 months), significantly inferior to patients with idiopathic hypereosinophilic syndrome with no identifiable mutations (median disease-specific survival: not reached, 0.6-405.3 months, P o0.001), but not statistically different from idiopathic hypereosinophilic syndrome patients with mutations (not reached, 1.0-223.9 months, P = 0.117).…”
Section: Discussionmentioning
confidence: 99%
“…Although this may be due to the relatively small number of patients with mutations that limited the statistical power, several other explanations are also plausible. The nextgeneration sequencing assays used in this study targeted genes that are known to be mutated with relatively high frequency in myeloid neoplasms; although with good gene coverage, some relevant genes were either not included, such as abovementioned PUF60 and CDH17, 26 or only tested in a subset of patients, such as SETBP1 and CSF3R. We may have found mutations in idiopathic hypereosinophilic syndrome/next-generation sequencingnegative patients if whole genome sequencing or a more extensive next-generation sequencing panel had been performed.…”
Section: Discussionmentioning
confidence: 99%
“…The eosinophil proteome has been preliminarily mapped out, and eosinophils have been shown to regulate the intestinal microbiome . De novo mutations and genome wide methylation patterns responsible for HES have been initiated . The EoE transcriptome has been uncovered, providing new insight into disease pathogenesis and providing the framework for a diagnostic PCR‐based diagnostic panel .…”
Section: Resultsmentioning
confidence: 99%
“…18 De novo mutations and genome wide methylation patterns responsible for HES have been initiated. 116 The EoE transcriptome has been uncovered, providing new insight into disease pathogenesis and providing the framework for a diagnostic PCR-based diagnostic panel. 108,117 Such an approach has facilitated new drug development such as anti-Type 2 cytokine therapy.…”
Section: "Omics"mentioning
confidence: 99%
“…Somatic missense mutations were found in three patients, including spliceosome gene PUF60 and the cadherin gene CDH17. In addition, they showed that aberrant DNA methylation patterns can distinguish clonal from reactive eosinophilia, which may be very useful in daily clinical work (Andersen et al, 2015). Other study used targeted nextgeneration sequencing panels designed for myeloid neoplasms to bone marrow specimens from a cohort of 51 idiopathic HES patients and 17 CEL-NOS patients (Wang et al, 2016).…”
Section: Notementioning
confidence: 99%